2007
DOI: 10.1037/0022-3514.93.6.1108
|View full text |Cite
|
Sign up to set email alerts
|

Gender and sexual orientation differences in sexual response to sexual activities versus gender of actors in sexual films.

Abstract: In this study, the authors investigated the hypothesis that women's sexual orientation and sexual responses in the laboratory correlate less highly than do men's because women respond primarily to the sexual activities performed by actors, whereas men respond primarily to the gender of the actors. The participants were 20 homosexual women, 27 heterosexual women, 17 homosexual men, and 27 heterosexual men. The videotaped stimuli included men and women engaging in same-sex intercourse, solitary masturbation, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
275
8
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(320 citation statements)
references
References 77 publications
(126 reference statements)
36
275
8
1
Order By: Relevance
“…than a heterosexual stimulus, depicting a man and a woman; likewise, for homosexual men a pure male sexual stimulus, depicting two men, elicits more arousal than a heterosexual stimulus (Chivers et al, 2004;Chivers et al, 2007). Moreover, responses to heterosexual stimuli do not indicate whether arousal was to the male, the female, or both sexes, a question of particular importance for the present research.…”
Section: Methodsmentioning
confidence: 68%
See 1 more Smart Citation
“…than a heterosexual stimulus, depicting a man and a woman; likewise, for homosexual men a pure male sexual stimulus, depicting two men, elicits more arousal than a heterosexual stimulus (Chivers et al, 2004;Chivers et al, 2007). Moreover, responses to heterosexual stimuli do not indicate whether arousal was to the male, the female, or both sexes, a question of particular importance for the present research.…”
Section: Methodsmentioning
confidence: 68%
“…This is achieved by assessing changes in penile circumference or volume with gauges worn by participants (Janssen, 2002(Janssen, , 2011. Genital arousal is a strong indicator of male sexual orientation in the sense that heterosexual men exhibit almost exclusive genital arousal to women but not to men, and homosexual men exhibit almost exclusive genital arousal to men but not to women (Chivers, Seto, & Blanchard, 2007;Freund, Langevin, Cibiri, & Zajac, 1973;Rieger et al, 2005;Sakheim, Barlow, Beck, & Abrahamson, 1985). Because men's genital arousal to sexual stimuli is less likely under their conscious control than their self-reported sexual attraction to these stimuli (Janssen, 2011), it is preferred to self-report by researchers who seek an automatic measure of male sexual attraction and arousal (Seto, 2004).…”
Section: Measurement Of Sexual Arousalmentioning
confidence: 99%
“…The fact that social comparison judgments are processed differently by men compared to women (or that men place less emphasis on certain kinds of social comparisons, such as those about relative levels of physical attractiveness of potential male conspecifics), may also influence viewing time patterns as found here (that is, gender-nonspecificity among women and gender-specificity among men). Moreover, although this finding could improve the current understanding of gender differences in gender-specificity in sexual interest using unrestricted viewing time paradigms (both the pictures and sexual attractiveness rating scale were presented until participants rated the pictures), it cannot explain women's weaker gender-specificity in sexual interest using restricted viewing time paradigms (in which the pictures were presented for 750/500 ms, then removed and followed by the sexual attractiveness rating scale; more details were reported in Imhoff et al,2010) and women's genital sexual arousal (e.g., Chivers et al, 2007;Peterson et al, 2010). (Park et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Although some research has shown that both heterosexual men and women are gender-specific in subjective sexual arousal (Chivers, Blanchard, & Seto, 2007;Chivers & Timmers, 2012), a number of studies have indicated that heterosexual men tend to be more gender-specific in their genital sexual arousal and sexual interest than heterosexual women. That is, heterosexual men's genital sexual arousal and sexual interest tend to be greater to sexual stimuli depicting women, whereas relative to men, women's genital sexual arousal and sexual interest tend to be similar to sexual stimuli depicting either men or women (Cerny & Janssen, 2011;Chivers, 2005;Lippa, 2013;Lippa, Patterson, & Marelich, 2010;Rieger, Chivers, & Bailey, 2005;Suschinsky, Lalumière, & Chivers, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…on a 7-point Likert-type scale (0 = no arousal at all; 6 = extremely sexually aroused). The one-item scale used in the present study is similar to those used and validated in previous studies on subjectively reported sexual arousal 52,53 .…”
Section: Sem Consumptionmentioning
confidence: 95%